Frontline + The Machine: Comparing the Sociotechnical Realities of Centralized & Franchised Digital Strategies in International Hospitality - El Dimassi,Hamzah; Owensby,Sarah Zata Amani; Walter Molina,Carl (2026)
This thesis examines how contrasting corporate digital strategies shape frontline hotel employees’ ability to balance chain-level systems with local service responsiveness. The study treats chain-level digital systems as contemporary fixed elements of hotel formats by applying and building up on the Integration-Responsiveness framework, Flexible Replication, and sociotechnical perspectives, in particular the TOP framework and the principle of joint optimization. Empirically, it compares two international hotel groups that differ in both digital systems used and ownership model. One is a corporately owned chain using a central configured, highly connected cloud ecosystem, while the other is a family-owned franchise that is operating a large-scale, compliance-oriented platform. The study adopts a qualitative and abductive research approach, combining semi-structured interviews with frontline and local managerial staff in both properties and secondary sources from corporate and vendor materials. For each group across the Technology, Organization, and People pillars, the Gioia method is used for identifying the aggregate dimensions to develop a comparative discussion. The findings show that while centralized deployment generates frictionless automation, it intensifies the visibility and psychological pressure on staff. Whereas the franchise standardization preserves analog hospitality by shifting operational and cognitive burdens onto the frontline. The thesis contributes to international business and hospitality research by demonstrating how digital infrastructure and organizational structure together shape the possibilities for local service adaptation.
Keywords: hospitality; international hotels; digitalisation strategy; flexible replication; digital systems; sociotechnical; sociotechnical systems; joint optimization; local responsiveness